Cognitive analytic therapy for high-risk sexual behaviour. Issue 1 (2nd January 2016) - Sacks, Maxine; Jagielska-Hall, Dorota; Jeffery, Sophie
ABSTRACT: Sexually transmitted infections (STIs), including HIV, are a growing problem in the UK. The NICE Guidelines (2007 ) recommend interventions based on behaviour change models to prevent transmission of STIs and HIV. However, these approaches are often not sufficient to help clients make changes. To meet this need, cognitive analytic therapy (CAT) was trialled in a sexual health clinic with clients at high risk of contracting or transmitting STIs. Following the therapy, clients reported that they were more able to understand their risky behaviour and achieve change. This paper describes the work and outlines relevant elements of the CAT model.